Clinical case of acute myeloblastic leukemia with t(8;21)(q22;q22) in a patient with Klinefelter’s syndrome - Vanya Slavcheva; T. Lukanov; G. Balatsenko; S. Angelova; А. Antonov; L. Bogdanov; N. Tsvetkov (Hematology Reports, 2010)
Klinefelter’s syndrome is characterized by abnormal karyotype 47, XXY and a phenotype associated with hypogonadism and gynecomastia. Often the disease can be diagnosed accidentally, when carrying out cytogenetic analysis in cases of a malignant blood disease. We present the clinical case of a patient diagnosed with acute myelomonoblastic leukemia- M4 Eo (AML- M4), where by means of classic cytogenetics a karyotype was found corre-sponding to Klinefelter’s syndrome. Three induction courses of polychemotherapy wermade, which led to remission of the disease, documented both flowcytometrically and cytogenetically.